Trust and reputation ontologies for electronic business - Schmidt, S.; Dillon, Tharam S.; Steele, R.; Chang, Elizabeth (INSTICC, 2007)
The emergeonce of social networks in centralized and distributed virtual communities is one of the hottest topics in today's research communities. Trust and reputation ontologies which capture the social relationships and concepts among interacting parties offer a standardized and common understandin of a problem domain such as electronic business in autonomous environments. To improve interoperability, ontologies can be shared among interacting agents and form the basis for many of the autonomous activities of intelligent agents. The oncologies presented in this paper concentrate on the formalisation of business discovery, business selection, and business interaction QoS review concepts. Special focus is put on trust and reputanon relationships which form among the entities involved.